Social Responsibility in CEMEX - García-Muñoz-Aparicio, Cecilia (2020)
The article describes an analysis of the social responsibility of the economic group CEMEX, which, through its leadership and strategies, has come to be recognized as a world organization in the construction area; and for their responsible actions with society, the environment, vulnerable communities, and others. A qualitative methodology was used with a descriptive thematic analysis; a bibliographic review that includes: articles, studies, news, and the web, on the social responsibility of the organization worldwide, whose objective was to analyze the way in which its actions and strategies impact society and the environment. t is concluded that the economic group, although it has had some failures before society, constitutes a great innovative company that meets social and research objectives, promoting improvement programs in relation to sustainable development, and changes to make a better world through social responsibility. Keywords: CEMEX, social responsibility and programs.